x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

24 visualizzazioni (ultimi 30 giorni)
cadburry oreo
cadburry oreo il 4 Ott 2020
Risposto: Jonas il 8 Feb 2023
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

Risposte (1)

Jonas
Jonas il 8 Feb 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

Categorie

Scopri di più su Systems of Nonlinear Equations in Help Center e File Exchange

Tag

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by